Lifetime fitness consequences of early‐life ecological hardship in a wild mammal population. Issue 6 (12th February 2017) - Marshall, Harry H.; Vitikainen, Emma I. K.; Mwanguhya, Francis; Businge, Robert; Kyabulima, Solomon; Hares, Michelle C.; Inzani, Emma; Kalema‐Zikusoka, Gladys; Mwesige, Kenneth; Nichols, Hazel J.; Sanderson, Jennifer L.; Thompson, Faye J.; et al.
Abstract: Early‐life ecological conditions have major effects on survival and reproduction. Numerous studies in wild systems show fitness benefits of good quality early‐life ecological conditions ("silver‐spoon" effects). Recently, however, some studies have reported that poor‐quality early‐life ecological conditions are associated with later‐life fitness advantages and that the effect of early‐life conditions can be sex‐specific. Furthermore, few studies have investigated the effect of the variability of early‐life ecological conditions on later‐life fitness. Here, we test how the mean and variability of early‐life ecological conditions affect the longevity and reproduction of males and females using 14 years of data on wild banded mongooses ( Mungos mungo ). Males that experienced highly variable ecological conditions during development lived longer and had greater lifetime fitness, while those that experienced poor early‐life conditions lived longer but at a cost of reduced fertility. In females, there were no such effects. Our study suggests that exposure to more variable environments in early life can result in lifetime fitness benefits, whereas differences in the mean early‐life conditions experienced mediate a life‐history trade‐off between survival and reproduction. It also demonstrates how early‐life ecological conditions can produce different selection pressures on males and females. Abstract : The mean and variability of early‐life ecological conditions may have differing effects on life‐history trade‐offs and can have sex‐specific effects. Male banded mongooses born in better early‐life conditions invested more in reproduction but lived shorter lives, that is, "live‐fast, die‐young"; however, males born in more variable conditions lived longer and had greater reproductive success. We found no such effects in females.